Heat shock protein 70 (HSP70) expression in antimony susceptible/resistant clinical isolates of Leishmania donovani - Maharjan, Mahendra; Madhubala, Rentala (Nepal Journal of Biotechnology, 2015)
Pentavalent antimonials have long been the first line of defence against leishmaniasis, but resistance has been reported in different parts of the world. Pentavalent antimony is reduced into trivalent form in the cells and is a potential inducer of HSP70 in L. donovani. Expression profile of HSP70 in antimony susceptible and resistant L. donovani isolates were characterized by Southern blot, Northern blot and western blot analysis. HSP70 gene copy number, gene expression and HSP70 protein expression was found uniform in both antimony sensitive and resistant clinical isolates. In laboratory condition, Leishmania cells respond to antimonial drug stress by three fold over expression of the HSP70 protein. The observed results indicated that HSP70 play important role in stress tolerance against antimonial drug without differential expression in antimony sensitive and resistance clinical isolates of L. donovani. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 22-28